The integration of knowledge among academics at the International Islamic University Malaysia (IIUM) - Mamat , Arifin; Hussien, Suhailah; Che Haron, Sueraya (2013)

(untitled)
Educational system in Muslim countries is largely characterized by secular or Western ways of thinking and judging. Muslims have ended up as passive consumers, particularly of ideas coming from the dominant Western civilization. In response to that, Muslim intellectuals have called for a process of integration or Islamization of knowledge. The International Islamic University Malaysia (IIUM) has always been committed to the integration of Islamic values with the modern fields of knowledge. Therefore, this study attempts to investigate academics perceptions toward Islamization of knowledge, examine their practices of integration in the IIUM curriculum and establish indicators to measure the integration of knowledge. A purposive sampling, consisting of 306 academics from different Kulliyyahs in IIUM was selected. The study employs a survey method, where a self-constructed questionnaire was developed. A simple descriptive statistical analysis which includes percentages, frequencies and means was used for data analysis. Findings of the study show that respondents have a good awareness about the integration of knowledge in IIUM. They believe that the integration of knowledge is an important mission and a unique experience of IIUM. In this study the researchers came to the conclusion that there are four main indicators for integration of knowledge in IIUM. The indicators are; contents of the subject, the teaching and learning process, the assessment of integration of knowledge and the product/outcome of integration of knowledge. The study reveals that respondents integrate contents of the subjects with several Islamic values. The most frequent method applied in the teaching and learning process was through exemplifications and evidence provision. However the assessment of IOK was mostly done through classroom presentations. In addition, the study also reveals that the highest product/outcome of integration of knowledge is students’ assignments. The study suggests recommendations to enhance the integration of knowledge in IIUM. One of which is to constantly promoting integration of knowledge among staff of IIUM and also crystalizing the process and procedures of integration of knowledge to academic staff.